A Preliminary Evaluation of the Psychometric Properties of the ARTIC‐10 in Dental Settings: A Cross‐Sectional Study - Freddie O'Donald; Molly Smith; Lindsay‐Jo Sevier‐Guy; Abigail Heffernan (Health Science Reports, 2025)
Abstract Background and Aims Trauma‐informed care (TIC) is increasingly recognized in healthcare, including dentistry, for its potential to improve patient outcomes. However, there are currently no validated tools for assessing TIC attitudes among dental professionals. This study aimed to evaluate the psychometric properties of the 10‐item Attitudes Related to Trauma‐Informed Care (ARTIC‐10) scale within a UK dental hospital setting and explore its ability to distinguish between staff with and without prior TIC training. Methods A cross‐sectional study was conducted with 43 staff members from a UK dental hospital, including dentists, dental nurses, administrative staff, and technicians. Participants completed the ARTIC‐10 and the Beliefs About Trauma and Trauma‐Informed Care (BAT‐TIC) scale. A subset of participants (n = 13) completed the ARTIC‐10 again after 1 month to assess test–retest reliability. Internal consistency, construct validity, test–retest reliability, and group differences were examined. Results The ARTIC‐10 demonstrated strong test–retest reliability (intraclass correlation coefficient = 0.891) and moderate construct validity through a significant positive correlation with the BAT‐TIC (r = 0.493, p = 0.005). TIC‐trained staff scored significantly higher on the ARTIC‐10 (M = 5.30, SD = 0.73) than untrained staff (M = 4.84, SD = 0.73), t(41) = 2.03, p = 0.04, with a moderate effect size (d = 0.62). However, internal consistency was low (Cronbach's α = 0.420), suggesting limitations in scale reliability within this sample. Conclusion The ARTIC‐10 shows preliminary promise as a measure of trauma‐informed attitudes among dental staff and may be useful in evaluating training interventions. However, further research with larger, stratified samples is needed to improve internal consistency and assess the scale's broader applicability in dental settings.